Development of religious tourism and history of Complex Syekh Burhanuddin tomes in Nagari Ulakan, District Padang Pariaman - Hayati Otari; Siti Fatimah (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2018)
This research begins with the observations and observations of the author when visiting Syekh Burhanuddin Nagari Ulakan's Religious Cemetery of Ulakan Tapakis Subdistrict, Padang Pariaman Regency, that unknown attractions, narrow accessibility, inadequate tourist facilities and tourist activities in tourist attractions Religious Tomb of Sheikh Burhanuddin. This study aims to analyze how the Development of Religious Tourism and the History of Syekh Burhanuddin's Tomb in Padang Pariaman Regency is seen from four indicators of development potential, namely attractions, accessibility, amenities, and activities. This type of research is a qualitative method research using SWOT analysis. The technique of data collection is done using the method of interview, observation, documentation, and SWOT analysis. The technique of data collection was done by interviewing the tomb guards and those who knew more about Sheikh Burhanuddin's grave, and using the SWOT analysis. Religious activity in the area has brought vast impact on the surrounding region, either in the form of the development of economic activities, the development of settlements and the like, however the development of the area has not been coupled with completeness basic facilities and infrastructure are adequate in supporting religious activities as well as a growing tourism activities.